Primulina longiflora (Gesneriaceae), a new species from Guangxi, China - Tong, Yi-Hua; Ni, Jing-Bo; Wang, Bing-Mou (Phytotaxa, 2025)
Primulina longiflora, a new species endemic to Guangxi, China, is described and illustrated. The new species is most similar to P. curvituba in the shape and texture of leaf blades and the curved corolla tube, but mainly differs in having longer calyx lobes, salverform and much longer corolla, and the bifid lower stigma lobe. Conservation status and discussions on differences between this new species and morphologically similar species are also provided.